VICTIMIZATION OF VIOLENCE AGAINST CHILDREN AND ITS PREVENTION - Niyozova Salomat Saparovna (International Journal of Business, Law and Political Science, 2026)
Objective: This study examines violence against children as a persistent social and legal problem that threatens minors’ physical, psychological, and moral development and undermines the effective realization of their fundamental rights. While existing scholarship has extensively analyzed offender profiles, particularly cisgender male perpetrators, the victimological–ecological characteristics of child victims and their role in the emergence, concealment, and recurrence of violence remain insufficiently explored. Method: The research employs a qualitative legal and criminological approach, drawing on the analysis of national legislation, doctrinal literature in victimology and criminology, judicial and investigative practices, and findings from forensic psychological and psychiatric examinations. Systemic, logical, and comparative methods are used to identify victimogenic factors arising from interactions among offenders, victims, and their social environments. Results: The findings demonstrate that child victimization is strongly influenced by age-related psychological vulnerability, dependency on offenders, exposure to family violence, emotional instability, and structurally embedded helplessness. These victimogenic characteristics not only increase susceptibility to violence but also facilitate crime concealment and heighten the risk of severe consequences, including suicidal behavior. Novelty: This study advances victimological scholarship by shifting the analytical focus from offender-centered explanations to an integrated victimological–ecological framework, emphasizing prevention through early risk identification, reinforcement of protective factors, and coordinated legal, psychological, and social interventions.